Vocational Education and Training in the Age of Digitization Challenges and Opportunities - Wuttke, Eveline; Seifried, Jürgen; Niegemann, Helmut M. (Research in Vocational Education, 2020)
The increasing digitization of the world of work is associated with accelerated structural changes. These are connected with changed qualification profiles and thus new challenges for vocational education and training (VET). Companies, vocational schools and other educational institutions must respond appropriately. The volume focuses on the diverse demands placed on teachers, learners and educational institutions in vocational education and training and aims to provide up-to-date results on learning in the digital age.